Quality performance of educational programme resources based on MOHE’s implementation of quality assurance standards / Norhidayah Ali, Zuraidah Mohamed Isa and Dahlia Ibrahim - Ali, Norhidayah; Mohamed Isa, Zuraidah; Ibrahim, Dahlia (Research Management Institute, 2010)
The rising need of higher education has led to the introduction of Quality Standard Assurance regulation by Ministry of Higher Education (MOHE) forcing universities to seriously commit themselves in providing high quality education to their students. Higher education institutions (HEI) are required to regularly review the quality of education and services rendered to their students. In the past, there was no special study focusing on the quality of education taking into account evaluations particularly from students’ perspective. Therefore, this study is attempted to assess quality performance on the basis of educational program resources in selected Malaysia’s Northern public universities. Researchers focused on variables such as general facilities, library system and education program in relation to the study. Generally, this study attempted to examine in what ways do these variables (general facilities, library system and education program) contribute to the quality performance of the educational program resources. The researchers used descriptive analysis, factor analysis (KMO and Bartlett’s Test), reliability and correlation analysis in order to evaluate the data collected. From the findings, it was concluded that there was strong relationship between quality performance and the independent variables under study. It is, hence, suggested that these aspects should be given priority if the higher institutions want to meet students’ expectation of quality. However, further research should be done on other areas of quality as specified by MOHE in order to maximize the performance of HEI.